إشكالية وظيفة إدارة الموارد البشرية في المصارف الإسلامية - بن معزوز، كمال; مخباط ،سارة (جامعة الوادي University of Eloued, 2025)
عرف قطاع الصيرفة الإسلامية تطور كبير خلال الثلاثون سنة الماضية، غير أن هذا التطور لم يكن مصحوب بما يسد حاجياته من الموارد البشرية الملائمة لهذا النشاط التمويلي المتميز المرتكز على أحكام الشريعة الإسلامية. في هذا الصدد ارتكزت الدراسة على ابراز مميزات المصارف الإسلامية واحتياجاتها من ناحية المورد البشري الكفء والمناسب، ومدى مواكبة المصارف والجامعات لهذ التطور من خلال دريب وتوفير الكفاءات في هذا المجال. على الرغم من الجهود المبذولة ورؤوس الأموال المستثمرة من طرف المصارف الإسلامية في تدريب وتطوير العاملين، إلا أن ذلك لم يكن كافيا لتلبية حاجيات هذا القطاع من الموارد البشرية المؤهلة. حيث هناك فجوة بين الجانب المهني المتمثل في المؤسسات المالية الاسلامية والجانب العلمي الأكاديمي المتمثل في الجامعات ومؤسسات التكوين الشرعي. The Islamic finance sector has known a significant growth over the past thirty years; however, this growth has not been accompanied by the necessary and adequate human resources to face the needs of this particular activity based on the principles of the Islamic law. Our study focused on the characteristics of financial banks and their needs in terms of qualified human resources, and how are banks and universities keeping up with this evolution by training and providing competences required in this field . Despite the efforts and capital invested by Islamic banks in the training and development of their employees, this has not been sufficient to meet the sector's requirements in qualified human resources, where there is a gap between the professional side the represents Islamic financial institutions and, the Scientific academic side that represents universities and Islamic training institutions.
The problematic of the human resources management in Islamic banks
مقال
Keywords: المصرف الإسلامي; إدارة الموارد البشرية; رأس المال البشري; الشريعة الإسلامية، التكوين; Islamic bank; Human resources management; Human capital; Islamic law